Revisit on ion acceleration mechanisms in solid targets driven by intense laser pulses. (30th November 2018) - Qiao, B; Shen, X F; He, H; Xie, Y; Zhang, H; Zhou, C T; Zhu, S P; He, X T
Abstract: The most investigated ion acceleration mechanisms in solid targets driven by intense laser pulses are revisited, including the target normal sheath acceleration (TNSA), radiation pressure acceleration (RPA), hybrid scheme of radiation pressure-sheath acceleration and Coulomb explosion (CE). In these acceleration mechanisms, the competition, between thermal pressure, radiation pressure and electrostatic pressure, decides the acceleration dynamics. Thermal pressure induced by hot electrons dominates TNSA, while RPA is ideally driven by steady radiation pressure and CE is mainly governed by the electrostatic pressure stored in the target. Two-dimensional particle-in-cell simulations are performed to display and elucidate this dynamical evolution among different mechanisms by changing the target thickness.